The Antibacterial Activity Of Conventional Serum And Nano Face Serum From Pineapple Stem Extract (Ananas Comosus (L.) Merr) Against Staphylococcus Epidermidis - Minda Sar Lubis; Asmarani, Asmarani; Rafita Yuniarti; Haris Munandar Nasution (Jurnal EduHealth, 2024)
Pineapple hump has been identified to contain secondary metabolites in saponin, flavonoid, and steroid/triterpenoid which show potential as antibacterial agents against Staphylococcus epidermidis. These bacteria are part of the normal composition of gram-positive bacteria on human skin and do not display any pathogenic characteristics. Even so, these bacteria can trigger facial skin infections, especially in the form of pimples which are often difficult to treat. This study aimed to determine the differences in bacterial inhibition of cosmetic preparations in the form of conventional serum and nano serum from pineapple hump extract (Ananas comosus (L.) Merr) against bacteria Staphylococcus epidermidis. This research uses the method of True Experimental. In this study, pineapple hump was extracted and formulated into conventional serum preparations and nano serum with various concentrations, then tested for its antibacterial activity against the bacteria Staphylococcus epidermidis. Diameter of antibacterial inhibition of conventional Serum Pineapple hump Extract against bacteria Staphylococcus epidermidis i.e., Blank has no inhibition, 2% concentration (10.10 mm), 10% concentration (11.28 mm) and 20% concentration (13.26 mm). The diameter of inhibition of Nano serum Pineapple Hump Extract, namely Blank, had no inhibition, 2% concentration (10.44 mm), 10% concentration (11.56 mm) and 20% concentration (15.14 mm). The positive control for Clindamycin had an inhibitory effect (32.8 mm), the positive control for the circulating Pineapple Hump Extract (15.52 mm) and the negative control had no inhibition.